Kolaborasi Alat Musik Tradisional dan Alat Musik Modern dalam Mengiringi Ibadah Minggu di Huria Kristen Batak Protestan Tanjung Sari Medan - Bella Cindy Juwita Simanjuntak; Pulumun Peterus Ginting; Wiflihani Wiflihani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
This study discusses the collaboration of traditional musical instruments and modern musical instruments in accompanying Sunday services at HKBP Tanjung Sari Medan. The purpose of this study was to find out the background and process of collaboration of traditional musical instruments and modern musical instruments in the HKBP Tanjung Sari church in Medan. The method used in this study is qualitative descriptive. The location of the study was carried out at the Tanjung Sari HKBP church, Jl. Setia Budi No. 11, Medan. The population of this study is traditional musical instruments and modern musical instruments used in accompanying Sunday services at HKBP Tanjung Sari Medan. While the samples in this study were Taganing, drums, keyboards, acoustic guitars, bass guitars, saxophone which were used to accompany Sunday services at HKBP Tanjung Sari Medan. The data collection technique is through observation, interviews, documentation, and library studies. Based on the results of the study, it can be seen that traditional musical instruments and modern musical instruments used in accompanying Sunday services at HKBP Tanjung Sari Medan, namely: Taganing, drums, keyboards, acoustic guitars, bass guitars, saxophone. The songs used in accompanying Sunday Service at HKBP Tanjung Sari Medan, and the collaboration process of traditional musical instruments and modern musical instruments in the HKBP Tanjung Sari church in Medan.